Prevalence, Associated Factors and Outcome of Newborns with Anaemia as Seen in Rivers State University Teaching Hospital, Nigeria - , Boma Awoala West; , Adaku Arthur; , Josephine Enekole Aitafo; , Hannah Omunakwe (Archives of Current Research International, 2021)
Aim: There is paucity of literature on the prevalence of neonatal anaemia globally thus aim of the study was to evaluate the prevalence, determine the associations and the clinical outcome of neonates with anaemia. Study Design: This was a descriptive prospective cross-sectional study. Place and Duration of Study: Study was carried out among neonates admitted in the Special Care Baby Unit of Rivers State University Teaching Hospital over one year. Methodology: A convenient sampling size of 402 neonates who met the inclusion criteria were consecutively recruited. Data was analysed using SPSS version 23. Results: Of 402 neonates assessed, 106(26.4%) had anaemia with PCV less than 42%. Anaemia was observed more in males 56(52.8%), neonates delivered via Caesarean section 74(69.8%) and at gestational age less than 37 weeks 53(50%). Mild anaemia was observed mostly, 66(62.3%). Common pregnancy complications of mothers with anaemic babies were prolonged rupture of membranes 17(35.4%) and hypertension in pregnancy 14(29.2%) while the commonest morbidities in these neonates were probable sepsis 65(63.8%), neonatal jaundice 53(52%) and prematurity 53(52%). There was significant difference in anaemic and non-anaemic neonates with regards to mothers with gestational diabetes (P value < 0.0001). The factors associated with severe anaemia were probable sepsis and the duration of stay. Blood transfusion was carried out in 27(25.5%) neonates. An overall mortality of 7.5% was documented, severe anaemia being highest (21.4%). Conclusion: The prevalence of anaemia was high being 26.4% and was observed more in males, preterms and babies delivered via Caesarean section. There was significant difference in anaemic and non-anaemic neonates with regards to mothers with gestational diabetes. Probable sepsis and duration of stay were significantly associated with severe anaemia. The mortality rate in neonates with anaemia was 7.5% thus there is need to assess newborns for anaemia with prompt intervention to prevent morbidity, mortality and long term sequelae.